Senam Ergonomis Meningkatkan Kualitas Tidur Lansia - Khoiriyah, Umi Musrifatul; Kurnia, Rina (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: The elderly are people aged 60 years and over and experience the aging process which will affect the quality of sleep to be less good or bad. One way to overcome poor quality is to do non-pharmacological therapy ergonomic gymnastics which is useful for maintaining physical and psychological health which can relax the body so that sleep quality improves. Objectives: This study aims to determine the effect of ergonomic gymnastics on the quality of elderly sleep in Dukuh Gunden, Balak Village, Cawas District, Klaten Regency. Methods: This study uses a quantitative method with a pre-experimental design of one group pretest-posttest type. The sampling technique used was purposive sampling, with a total of 30 samples. Using the Pittsburghh Sleep Quality Index (PSQI) instrument. Ergonomic gymnastics intervention was carried out for 12 meetings. Hypothesis testing using Wilcoxon. Results: The sample amounted to 30 people with the highest age range of 60-74 years as many as 25 people (83.3%), male gender as many as 18 people (60%), the highest level of education was elementary school graduates as many as 20 people (66.7%), the elderly who lived with their families as many as 26 people (86.7%) and still had a partner as many as 23 people (76.7%). Based on body mass index, most elderly people have normal weight as many as 14 people (46.7%). The hypothesis result (p-value) of 0.000 so that p <0.05 means that there is an effect of giving ergonomic exercises on sleep quality in the elderly. Conclusion: Ergonomic gymnastics affects the quality of sleep of the elderly in Dukuh Gunden, Balak Village, Cawas District, Klaten Regency. Keywords: Ergonomic gymnastics, sleep quality, elderly.